Pembauran Agama dan Strategi Politik Kebudayaan: Kontestasi Identitas Etnis dalam Narasi Masyarakat Multikultur - Ibnu Mujib (UIN Maulana Malik Ibrahim Malang, 2008)
As a strategy of the politic of culture, religious assimilation constructed in New Order has become a concept which is considered ineffective and failed. The policy of the religious assimilation designed for reducing conflicts between